Selected Works of David Brillinger - Guttorp, Peter; Brillinger, David; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
This volume contains 30 of David Brillinger's most influential papers. He is an eminent statistical scientist, having published broadly in time series and point process analysis, seismology, neurophysiology, and population biology. Each of these areas are well represented in the book. The volume has been divided into four parts, each with comments by one of Dr. Brillinger's former PhD students. His more theoretical papers have comments by Victor Panaretos from Switzerland. The area of time series has commentary by Pedro Morettin from Brazil. The biologically oriented papers are commented by Tore Schweder from Norway and Haiganoush Preisler from USA, while the point process papers have comments by Peter Guttorp from USA. In addition, the volume contains a Statistical Science interview with Dr. Brillinger, and his bibliography.
Part 1: Theoretical Statistics -- Part 2. Time Series Papers -- Part 3. Population Biology and Environment -- Part 4. Point Processes.
Keywords: Statistics; Mathematical statistics; Statistics; Statistical Theory and Methods